New Dv-distance Method Based on Path for Wireless Sensor Network. Issue 2 (3rd April 2017) - Zhang, D. G.; Zhou, S.; Chen, J.
Abstract: Wireless location is one of the core technologies of Wireless Sensor Network. In many applications, the accuracy of the location is the precondition of the usefulness of data information the node collected. Under the premise of cost limits, improving the accuracy of wireless sensor node position has crucial significance. In this paper, after analyzing reasons of the location weakness of Dv-Distance method due to errors caused by different paths, we propose an estimation method that is based on the distance of different paths between node and the anchor node, thereby balancing the error of different paths to locate the node. This is an improved method, which is based on circle focal point positioning. The improved method is tested and its performance is analyzed in MATLAB. According to the test experiments, our method can improve the accuracy of positioning, and can reduce dependence on the number of nodes anchor.